Idarubicin-loaded biodegradable microspheres enhance sensitivity to anti-PD1 immunotherapy in transcatheter arterial chemoembolization of hepatocellular carcinoma. (February 2023) - Zheng, Zhiying; Ma, Mingxi; Han, Xiuping; Li, Xiao; Huang, Jinxin; Zhao, Yuetong; Liu, Hanyuan; Kang, Junwei; Kong, Xiangyi; Sun, Guoqiang; Sun, Guangshun; Kong, Jie; et al.
Abstract: Transarterial chemoembolization (TACE) is an image-guided locoregional therapy used for the treatment of patients with primary hepatocellular carcinoma (HCC). However, conventional TACE formulations such as epirubicin-lipiodol emulsion are rapidly dissociated due to the instability of the emulsion, resulting in insufficient local drug concentrations in the target tumor. To overcome these limitations, we used biodegradable Idarubicin loaded microspheres (BILMs), which were prepared from gelatin and carrageenan and could be loaded with Idarubicin (IDA-MS). The morphology and the ability to load and release IDA of BILMs were characterized in vitro. We evaluated tumor changes and side effects after TACE treatment with IDA-MS in VX2 rabbit and C57BL/6 mice HCC models. In addition, the effect of IDA-MS on the tumor immune microenvironment of HCC tumors was elucidated via mass spectrometry and immunohistochemistry. Result showed that IDA-MS was developed as a new TACE formulation to overcome the poor delivery of drugs due to rapid elimination of the anticancer drug into the systemic circulation. We demonstrated in rabbits and mice HCC models that TACE with IDA-MS resulted in significant tumor shrinkage and no more severe adverse events than those observed in the IDA group. TACE with IDA-MS could also significantly enhance the sensitivity of anti-PD1 immunotherapy, improve the expression of CD8 + T cells, and activate the tumor immune microenvironment in HCC. This study provides a new approach for TACE therapy and immunotherapy and illuminates the future of HCC treatment. Statement of significance: Conventional transarterial chemoembolization (TACE) formulations are rapidly dissociated due to the instability of the emulsion, resulting in insufficient local drug concentrations in hepatocellular carcinoma (HCC). To overcome these limitations, we used biodegradable microspheres called BILMs, which could be loaded with Idarubicin (IDA-MS). We demonstrated in rabbits and mice HCC models that TACE with IDA-MS resulted in significant tumor shrinkage and no more severe adverse events than those observed in the IDA group. TACE with IDA-MS could also significantly enhance the sensitivity of anti-PD1 immunotherapy, improve the expression of CD8 + T cells, and activate the tumor immune microenvironment in HCC. This study provides a new approach for TACE therapy and immunotherapy and illuminates the future of HCC treatment. Graphical abstract: Image, graphical abstract